Protective Effect of Adalimumab on Tissue Damage in Experimentally Induced Acute Pancreatitis - Yalnız, Fevzi Fırat; Eşkazan, Tuğçe; Ekçi, Baki; Çomunoğlu, Nil; Çoban, Jale; Pata, Cengiz; Erzin, Yusuf (Cerrahpaşa Medical Journal, 2021)
Objective: Tumor necrosis factor alpha (TNF-α) has a central role in acute pancreatitis pathogenesis and its related systemic complications. The aim of this study is to evaluate the therapeutic effectiveness of TNF-α inhibitor adalimumab (ADA) in severe necrotizing pancreatitis (SNP) model in rats. Methods: Seventy female Wistar albino rats were randomly divided into the following groups; group 1: SHAM laparotomy, group 2: SNP with modified SHOP model (MS-SNP), group 3: MS-SNP and saline intraperitoneally (IP), group 4: ADA 2 mg/kg IP + MS-SNP, group 5: ADA 4 mg/kg IP + MS-SNP, group 6: ADA 4 mg/kg IP and group 7: ADA 2 mg/kg IP. MS-SNP was induced by complete pancreatic duct obstruction and cerulein hyperstimulation (50 μm/kg IP). The subjects were sacrificed at the 24th hour, and then pancreatic amylase and edema, necrosis, inflammation, fat necrosis and bleeding parameters were evaluated. Results: When Group 4 and 5 were compared to Group 2, all histopathological scores were decreased. In group 4, only pancreatic edema, fat necrosis and total pathology scores were significantly lower than those of Group 2, on the other hand, all these parameters were significantly lower for Group 5 (P < .05). Pancreatic amylase levels were comparable between groups. Conclusion: Histopathological changes such as pancreatic edema, necrosis and bleeding were prevented by the administration of ADA, and the total pathology scores were found to be significantly lower in rats receiving ADA than the ones without ADA. The potential therapeutic role of ADA in acute pancreatitis should be evaluated in future studies. Cite this article as: Fırat Yalnız F, Eşkazan T, Ekçi B, et al. Deneysel akut pankreatit modelinde adalimumab’ın doku hasarını Önleyici etkisi. Cerrahpaşa Med J. 2021;45(2):116-123.